Virtual Daime: When Psychedelic Ritual Migrates Online - Hartogsohn, Ido (Frontiers in Psychology, 2022)
During the 2020 Covid-19 epidemic a variety of social activities migrated online, including religious ceremonies and rituals. One such instance is the case of Santo Daime, a Brazilian rainforest religion that utilizes the hallucinogenic brew ayahuasca in its rituals. During the pandemic, multiple Santo Daime rituals involving the consumption of ayahuasca took place online, mediated through Zoom and other online platforms. The phenomenon is notable since the effects of hallucinogens are defined by context (set and setting) and Santo Daime rituals are habitually governed by punctilious regulations aimed at directing the experience of participants. The abrupt move to online space thus augurs significant implications in the context of hallucinogenic rituals. This paper looks at this development and its repercussions for entheogenic rituals, as it asks how do psychedelic rituals change when they move online? Building on the author's previous work on set and setting in the Santo Daime religion, the paper introduces accounts from 12 semi-structured interviews with daimistas participating in online daime rituals, approached through the prism of set and setting, and the study of online religiosity. The analysis points at several key dynamics emerging in the context of virtual rituals. The migration online allowed for the continuation of Santo Daime entheogenic rituals at a time of social distancing, fostered a sense of global brotherhood and opened new possibility for religious participation and learning. Concurrently, online ritual produced an impoverished ritual experience and novel types of challenges including a higher potential for distractions, technical difficulties, and low sensory fidelity. Other novel challenges included social anxiety and an in-built tension between the social and spiritual dimensions of ritual. Finally, some participants were concerned by the cultural context of online rituals: technological mediation, consumerism, commodification, and digital divide. The limitations of digital technology appear amplified by the highly immersive, body oriented, experientially intensified context of the psychedelic experience. This paper contributes to the literature on the extra-pharmacological factors shaping experiences with psychedelics, as well as to the literature on the consequences of adoption of digital media technologies during the COVID-19 pandemic.